2006
DOI: 10.1021/ja057775y
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Chiral Imaging by Sum-Frequency Generation

Abstract: A sum-frequency generation (SFG) microscope that is sensitive toward molecular chirality was demonstrated for the first time. Optically active images of chiral 1,1'-bi-2-naphthol solutions were obtained with submicron spatial resolution. Three-dimensional sectioning capability of our microscope was also demonstrated. This optically active SFG microscopy can potentially become a powerful imaging technique for biological samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 18 publications
(33 reference statements)
1
62
0
1
Order By: Relevance
“…SFG measurements on aligned type I collagen have revealed that a symmetric methylene mode constitutes a major component of the achiral optical response, whereas carbonyl amide I vibrational modes are identified as chiral contributions in the SFG spectrum (50). Although these measurements have been performed only on macroscopic samples, similar experiments can be conducted in an optical microscope, providing access to detailed structural chemical information on a microscopic scale (44, 51). …”
Section: Vibrational Contrastmentioning
confidence: 99%
“…SFG measurements on aligned type I collagen have revealed that a symmetric methylene mode constitutes a major component of the achiral optical response, whereas carbonyl amide I vibrational modes are identified as chiral contributions in the SFG spectrum (50). Although these measurements have been performed only on macroscopic samples, similar experiments can be conducted in an optical microscope, providing access to detailed structural chemical information on a microscopic scale (44, 51). …”
Section: Vibrational Contrastmentioning
confidence: 99%
“…SFG is selectively sensitive to non-centrosymmetric structures. Ji et al constructed the first optically active SFG microscope, which allows chirality-sensitive, 3-D sectional images with submicron spatial resolution [35]. SHG is a special case of SFG in which the two excitation photons are degenerate.…”
Section: Overview Of Nlo Modalitiesmentioning
confidence: 99%
“…Subsequently, thin layers of enantiomeric BN solutions containing micrometer sized silica beads have been used to prove that chiral imaging is in principle possible from bulk samples by scanning for SFG intensities [7]. More recently, the authors of the present work have tried to probe the potential of this latter technique for solid samples using the same BN molecule trapped in a sol-gel matrix [8].…”
Section: Introductionmentioning
confidence: 96%